Handling information overload in a week - Griffiths, Andrea (Hodder & Stoughton, 1999)
Identifies a variety of information trends and habits, and suggests solutions for dealing with information overload. Topics addressed include: identifying the causes of overload; strategic and operational issues; developing personal filtering techniques; and building organisational competencies. This professional, practical and easy-to-use book is part of the popular "Successful in a Week" series.